On the Ethics of Capitalism - Hergouth, Martin (Filozofski vestnik, 2017)
General accounts of capitalist subjectivity usually (and most influentially) deploy the notion of alienation, understood as the general vanishing of any subjective dimension in the production process. However, in the contemporary, “post-Fordist”, form of capitalism, with its emphasis on the mobilisation of the subject as such, such an account of alienation is often obviously inadequate. The article therefore attempts to remedy this by sketching anew the conditions of the subject’s entry into the capitalist regime of action. To that end, we employ Hegel’s account of morality (as opposed to “ethical life”, or Sittlichkeit) and moral action in Phenomenology of Spirit. There, Hegel develops how the attempt at pure moral action, unbound by the ethical-social context of Sittlichkeit, gives rise to pathologies and failures of such action. We argue that the defining feature of capitalism is precisely the continuous erosion of such ethical context, which is why the actors in capitalism are continuously pressed into non-ethical, contextless action (such as in demands for “innovation” and “creativity”): the instabilities and uncertainties of the market-based recognition of activity in capitalism repeat the patterns of the pathologies of purely moral action described by Hegel. On this ground, we characterise the general mode of action in capitalism as compulsory irony, i.e. as a compulsion to act, which is not at the same time a compulsion to submit to some external purpose, but the compulsion to affirm the potential for action itself. This, however, turns out to be a quite different ethical disposition than the one described by the standard notion of alienation and is therefore, as we point out in the conclusion, a great obstacle to the inception of any general anti-capitalist political project.